Early Infectious Diseases Consultation and Procalcitonin-Guided Therapy Limits Unnecessary Antibiotic Use in COVID-19 - Kammeyer, Joel (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.